2018
DOI: 10.1186/s12864-018-4859-7
|View full text |Cite
|
Sign up to set email alerts
|

A correction for sample overlap in genome-wide association studies in a polygenic pleiotropy-informed framework

Abstract: BackgroundThere is considerable evidence that many complex traits have a partially shared genetic basis, termed pleiotropy. It is therefore useful to consider integrating genome-wide association study (GWAS) data across several traits, usually at the summary statistic level. A major practical challenge arises when these GWAS have overlapping subjects. This is particularly an issue when estimating pleiotropy using methods that condition the significance of one trait on the signficance of a second, such as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 26 publications
0
52
0
Order By: Relevance
“…Assume trait k is from cohort A with sample size n A and trait k′ is from cohort B with sample size n B , and there are n C overlapping subjects in these two cohorts. For any SNP j not associated with the traits, the correlation matrix of Z-score U kj = ffiffiffiffiffiffi V kj p among traits is invariant to SNP j 39,47 . In particular, if both traits k and k′ are quantitative, we have…”
Section: Methodsmentioning
confidence: 99%
“…Assume trait k is from cohort A with sample size n A and trait k′ is from cohort B with sample size n B , and there are n C overlapping subjects in these two cohorts. For any SNP j not associated with the traits, the correlation matrix of Z-score U kj = ffiffiffiffiffiffi V kj p among traits is invariant to SNP j 39,47 . In particular, if both traits k and k′ are quantitative, we have…”
Section: Methodsmentioning
confidence: 99%
“…The sample overlap between the GWAS on psychiatric disorders due to comorbidity should also be considered. This topic had previously been investigated using data from PGC (LeBlanc et al, 2018). They found that the overlap was less than 2% for eight psychiatric disorders.…”
Section: Limitationsmentioning
confidence: 99%
“…To the best of our knowledge, few studies have investigated overlapping-sample MR. Burgess et al [13] have shown that sample overlap increases type I error and leads to bias in classic MR methods. LeBlanc et al [14] have developed a correction method of overlapping samples by decorrelation. There is a pressing need for the development of a flexible MR approach that can be used for one-, two-as well as overlapping-samples.…”
Section: Introductionmentioning
confidence: 99%